Case Report: C3 deficiency in two siblings - Bernacchia, Agustín; Ginaca, Alejandra; Rotondo, Sabrina; Tejada, María Pilar; Di Giovanni, Daniela (Frontiers in Pediatrics, 2024)
The complement system, a vital component of innate immunity, consists of various proteins and pathways crucial for the recognition and elimination of pathogens. In addition, it plays a major role in the initiation of adaptive response through the opsonization of antigens, contributing to B cell activation and memory maintenance. Deficiencies in complement proteins, particularly C3, can lead to severe and recurrent infections as well as immune complex disorders. Here, we present a case report of two siblings with total C3 deficiency resulting from compound heterozygous mutations in C3 (NM_000064.4): c.305dup; [p.Asn103GlnfsTer66] and c.1269+5G>T, previously unreported in C3-related diseases. Both, the index case and her sister presented a history of recurrent infections since early childhood and one of them developed hemolytic uremic syndrome. Immunological evaluation revealed absent plasma C3 levels, decreased memory B cells, hypogammaglobulinemia, and impaired response to polysaccharide antigens. The siblings showed partial responses to antimicrobial prophylaxis and vaccination, requiring intravenous immunoglobulin replacement therapy, resulting in clinical improvement. Genetic analysis identified additional risk polymorphisms associated with atypical HUS. This case highlights the importance of comprehensive genetic and immunological evaluations in complement deficiencies, along with the potential role of immunoglobulin replacement therapy in managing associated antibody defects.